Identification of elastic edge parameters of plates using the method of fundamental solutions - Samandizade, Ehsan; Hematiyan, Mohammad-Rahim; Shiah, Yui-Chuin (Engineering analysis with boundary elements, 2025)
Free, fixed (clamped), and simply supported boundary conditions are standard edge boundary conditions that are normally considered in the modeling and analysis of plates. In many cases, the edge support of the plate is elastic, which cannot be modeled using the standard edge boundary conditions. To model the elastic edge of a plate, some parameters need to be determined. The aim of this study is to determine the elastic edge parameters of Reissner thick plates using inverse analysis. For the direct problem of a plate with an elastic edge, the method of fundamental solutions (MFS) formulated with the first-order shear deformation theory is used. An inverse method for determining the elastic edge parameters using measured displacements is presented. A gradient-based method is used for the optimization process in the inverse analysis. For the sensitivity analysis of elastic parameters, an analytical method based on the differentiation of governing equations is proposed. Two numerical examples for identifying elastic edge parameters in plates are presented and the effects of important parameters on the results are also investigated. Based on the results obtained, it is found that the proposed inverse method is very effective in identifying the elastic edge parameters.